NS3 genomic sequencing and phylogenetic analysis as alternative to a commercially available assay to reliably determine hepatitis C virus subtypes 1a and 1b. - Karin Neukam; Alfredo P Martínez; Andrés C A Culasso; Ezequiel Ridruejo; Gabriel García; Federico A Di Lello (PLoS ONE, 2017)
To evaluate the use of hepatitis C virus (HCV) NS3 sequencing as alternative to the comercially available Versant HCV 2.0 reverse hybridization line-probe assay (LiPA 2.0) to determine HCV genotype 1 (HCV-1) subtypes.A cohort of 104 patients infected by HCV-1 according to LiPA 2.0 was analyzed in a cross-sectional study conducted in patients seen from January 2012 to June 2016 at an outpatient clinic in Buenos Aires, Argentina.The samples were included within well supported subtype clades: 64 with HCV-1b and 39 with HCV-1a infection. Twenty of the HCV-1a infected patientes were included in a supported sub-clade "1" and 19 individuals were among the basal sub-clade "2". LiPA 2.0 failed to subtype HCV-1 in 20 (19.2%) individuals. Subtype classification determined by NS3 direct sequencing showed that 2/18 (11.1%) of the HCV-1a-infected patients as determined by LiPA 2.0 were in fact infected by HCV-1b. Of the HCV-1b-infected according to LiPA 2.0, 10/66 (15.2%) patients showed HCV-1a infection according to NS3 sequencing. Overall misclassification was 14.3% (κ-index for the concordance with NS3 sequencing = 0.635). One (1%) patient was erroneously genotyped as HCV-1 and was revealed as HCV genotype 4 infection.Genomic sequencing of the HCV NS3 region represents an adequate alternative since it provides reliable genetic information. It even distinguishes between HCV-1a clades related to resistance-associated substitutions to HCV protease inhibitors, it provides reliable genetic information for genotyping/subgenotyping and simultaneously allows to determine the presence of resistance-associated substitutions to currently recommended DAAs.